2021
DOI: 10.1101/2021.12.04.471211
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling implanted metals in electrical stimulation applications

Abstract: Background: Metal implants impact the dosimetry assessment in electrical stimulation techniques. Therefore, they need to be included in numerical models. While currents in the body are ionic, metals only allow electron transport. In fact, charge transfer between tissues and metals requires electric fields to drive the electrochemical reactions at the interface. Thus, metal implants may act as insulators or as conductors depending on the scenario. Objective/Hypothesis: The aim of this paper is to provide a theo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A floating potential boundary condition was imposed at the surface of active contacts with a current of ± 1 mA. Inactive contacts were set as electric insulation, according to a recent study where it was shown that metallic materials act as electric insulators when exposed to electric fields up to 100 V/m [11]. The point and line approximations (0D and 1D, respectively) were set respectively to a point or line current source of ± 1 mA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A floating potential boundary condition was imposed at the surface of active contacts with a current of ± 1 mA. Inactive contacts were set as electric insulation, according to a recent study where it was shown that metallic materials act as electric insulators when exposed to electric fields up to 100 V/m [11]. The point and line approximations (0D and 1D, respectively) were set respectively to a point or line current source of ± 1 mA.…”
Section: Methodsmentioning
confidence: 99%
“…The mesh comprised approximately 4 million tetrahedral finite elements with an average element quality of 0.57. The volume mesh was imported into Comsol, where appropriate electrical conductivities were assigned to each region: the head models were assigned to isotropic conductivity values as mentioned before, whereas the SEEG lead was assigned to a low conductivity, following [11]. Regarding the burr-hole in the skull and scalp, it was assigned to a conductivity of 1.79 S/m (same as CSF).…”
Section: Methodsmentioning
confidence: 99%
“…(see again Supplementary Material) show that when these factors are correctly modelled, the montage optimization algorithm can adjust the currents and electrode positions to account in part for the local increases of E-field under the skull defects. Such models can also be extended to include the effects of implants such as Ti plates (Mercadal et al, 2021a(Mercadal et al, , 2021b. It should be noticed, however, that it is hard to accurately segment accurately the scar tissue with MRI data alone, and the incorporation of CT data with robust segmentation algorithms for scar tissue would improve the models.…”
Section: Limitationsmentioning
confidence: 99%